DOP85 Efficacy of risankizumab rescue therapy in patients with moderately to severely active Crohn's Disease and inadequate response to risankizumab maintenance therapy. (21st January 2022) - Baert, F J; Atreya, R; Kakuta, Y; Long, M; Roblin, X; Neimark, E; Song, A; Wallace, K; Kingys, K; Mallick, M; Liao, X; Lim, A
Abstract: Background: The efficacy and safety of 12 weeks of induction and 52 weeks of maintenance treatment with risankizumab (RZB), an interleukin 23 p19 inhibitor, in patients with moderately to severely active Crohn's disease (CD) was previously demonstrated in 3 phase 3 trials (ADVANCE, MOTIVATE, and FORTIFY). We investigated outcomes in patients with inadequate response to subcutaneous (SC) RZB or SC placebo (PBO) treatment and required RZB rescue therapy during maintenance. Methods: In FORTIFY, a phase 3, double-blind, re-randomised responder withdrawal, maintenance study (NCT03105102), patients that responded to 12 weeks of RZB IV induction received RZB 180 mg SC, RZB 360 mg SC, or PBO (ie, withdrawal) every 8 weeks for 52 weeks. Starting at week 16, patients with inadequate response, defined as average daily stool frequency [SF] ≥ 3.3 and/or average daily abdominal pain score [APS] ≥ 1.5 as well as high-sensitivity C-reactive protein ≥ 5 mg/L and/or faecal calprotectin ≥ 250 μg/g; or Simple Endoscopic Score for CD (SES-CD) ≥ 6 (≥ 4 for isolated ileal disease), excluding the narrowing component as scored by the site Investigator, were eligible to receive open-label rescue therapy (1 dose of intravenous [IV] RZB 1200 mg, followed by RZB 360 mg SC every 8 weeks). Up to 2 rescue therapy visits ≥ 16 weeks apart were permitted. Efficacy at week 52 was assessed in the intent-to-treat population using nonresponder imputation for missing data. Patients were also considered nonresponders when maximum equivalent steroid dose exceeded the dose used at baseline or if patients initiated any new steroids. Safety was assessed throughout the study. Results: In the maintenance study, a greater proportion of patients in the withdrawal (PBO SC) arm (40.2% [66/164]) were administered RZB rescue therapy vs RZB 180 mg SC (24.2% [38/157]) and RZB 360 mg SC (21.3% [30/141]; Figure A ); most patients (71.1%–81.8%) required 1 rescue visit, and 16.7%–26.3% required 2 visits. Median time to first RZB rescue therapy was 178 days for the withdrawal (PBO SC) group, 179 days for the RZB 180 mg SC group, and 154 days for the RZB 360 mg SC group. At week 52, 52.5%–75.0% of patients who received RZB rescue therapy achieved SF/APS clinical response (Figure B ), and 20.0–36.4% of patients who received rescue therapy achieved clinical remission (per CDAI or SF/APS) and/or endoscopic response (Figures C-E ). The safety profile of RZB in CD has previously been reported. Conclusion: RZB rescue therapy (one dose of RZB 1200 mg IV followed by RZB 360 mg SC every 8 weeks) may be beneficial to patients with moderately to severely active CD experiencing inadequate response to or interruption in RZB maintenance treatment.